Sistem Pengenalian Manajemen Dalam Era Industri 5.0: Mewujudkan Organisasi Yang Agile dan Responsif - Eri Kusnanto; Sigit Pramono Hadi; Melvan Nisman Zega (Asosiasi Seni Desain dan Komunikasi Visual Indonesia, 2025)
The era of Industry 5.0 marks a paradigm shift in the global business landscape, integrating advanced technologies with human-centric values to create more agile and responsive organizations. This study explores the application of Management Control Systems (MCS) in the digital era, focusing on technologies such as artificial intelligence (AI), blockchain, and the Internet of Things (IoT). The research method involved conducting an interactive webinar via the Zoom platform, including material presentations, panel discussions, and Q&A sessions. Evaluation was carried out through participant feedback to improve the quality of future activities. The findings reveal that implementing digital technologies in MCS enhances operational efficiency, flexibility, and organizational competitiveness. However, challenges such as workplace culture resistance and cybersecurity risks remain significant obstacles. Proposed solutions include continuous training and interdisciplinary collaboration to support sustainable digital transformation. With the right strategic approach, organizations can leverage the opportunities of the Industry 5.0 era to achieve sustainability and innovation.